To solve this, we'll apply the distributive property to each term of the expression:
1/2(z + 4) - 3(1/3z + 1)
= (1/2 * z) + (1/2 * 4) - (3 * 1/3 * z) - (3 * 1)
= 1/2z + 2/2 - (3/3z) - 3
Now, let's simplify further:
= 1/2z + 1 - 1z - 3
Combining like terms:
= (1/2z - 1z) + (1 - 3)
= (-1/2z - 2)
So, the simplified expression is -1/2z - 2.
subtract 1/2 (z+4) - 3 ( 1/3 z +1). use fractions in final form.
3 answers
is this true?
Apologies for the incorrect solution. Let's reevaluate the expression:
Given expression: 1/2(z + 4) - 3(1/3z + 1)
= 1/2z + 1/2(4) - 3/1(1/3z) - 3/1(1)
= 1/2z + 1/2(4) - 3/1(1/3z) - 3/1
= 1/2z + 2/2 - 3/1(1/3z) - 3/1
= 1/2z + 2/2 - 3/3z - 3/1
= 1/2z + 1 - z - 3
= 1/2z - z + 1 - 3
= (1/2 - 1)z - 2
= -1/2z - 2
So, the correct simplified form is -1/2z - 2.
Given expression: 1/2(z + 4) - 3(1/3z + 1)
= 1/2z + 1/2(4) - 3/1(1/3z) - 3/1(1)
= 1/2z + 1/2(4) - 3/1(1/3z) - 3/1
= 1/2z + 2/2 - 3/1(1/3z) - 3/1
= 1/2z + 2/2 - 3/3z - 3/1
= 1/2z + 1 - z - 3
= 1/2z - z + 1 - 3
= (1/2 - 1)z - 2
= -1/2z - 2
So, the correct simplified form is -1/2z - 2.